The Perception of Morphological Awareness on Reading Comprehension in EFL Students: A Study on University-Level Strategies for Morphological Processing in Reading - Zidan Erky; Dzul Rachman; Rani Herning Puspita; Yeni Rahmawati (English Language Education Department, Universitas Majalengka, 2025)
This study investigates the perception of morphological awareness and its relationship to reading comprehension among EFL university students using a mixed-methods approach. A total of 57 participants completed questionnaires and reading comprehension tests, followed by interviews with 5 selected respondents. The quantitative findings revealed that students generally held positive perceptions of morphological awareness, with mean scores ranging from 2.84 to 3.28, and demonstrated strong reading comprehension performance (M = 80.24, SD = 6.014). A Pearson correlation analysis showed a statistically significant but modest positive relationship between morphological awareness and reading comprehension (r = 0.293, p = 0.027), and the questionnaire used had acceptable internal consistency (Cronbach’s Alpha = 0.744). The qualitative results reinforced these findings by illustrating that students frequently used morphological strategies such as word decomposition and contextual guessing to make sense of unfamiliar words. Participants also expressed that these strategies enhanced their reading confidence and reduced reliance on dictionaries or translation tools. Furthermore, many students advocated for greater emphasis on morphological instruction in English reading classes, especially in academic settings. These results suggest that morphological awareness contributes meaningfully to EFL learners’ reading development and supports the integration of morphology-based strategies in language education curricula.